Enhanced antitumor activity of bovine lactoferrin through immobilization onto functionalized nano graphene oxide: an in vitro/in vivo study - Azam Najmafshar; Mahboubeh Rostami; Jaleh Varshosaz; Dariush Norouzian; Seyed Ziyae Aldin Samsam Shariat (Taylor & Francis Group, 2020)
This study aims to improve the anticancer activity of bovine lactoferrin through enhancing its stability by immobilization onto graphene oxide. Bovine lactoferrin was conjugated onto graphene oxide and the conjugation process was confirmed by FT-IR, SDS-PAGE, and UV spectrophotometry. Physical characterization was performed by DLS analysis and atomic force microscopy. The cytotoxicity and cellular uptake of the final construct (CGO-PEG-bLF) was inspected on lung cancer TC-1 cells by MTT assay and flow cytometry/confocal microscopy. The anticancer mechanism of the CGO-PEG-bLF was studied by cell cycle analysis, apoptosis assay, and western blot technique. Finally, the anticancer activity of CGO-PEG-bLF was assessed in an animal model of lung cancer. Size and zeta potential of CGO-PEG-bLF was obtained in the optimum range. Compared with free bLF, more cytotoxic activity, cellular uptake and more survival time was obtained for CGO-PEG-bLF. CGO-PEG-bLF significantly inhibited tumor growth in the animal model. Cell cycle arrest and apoptosis were more induced by CGO-PEG-bLF. Moreover, exposure to CGO-PEG-bLF decreased the phospho-AKT and pro-Caspase 3 levels and increased the amount of cleaved caspase 3 in the treated cells. This study revealed the potential of CGO-PEG as a promising nanocarrier for enhancing the therapeutic efficacy of anticancer agents.